Съчинения на Григорий Цамблак във Вилнюски ръкописни сбирки - Кенанов, Димитьр (Kalbotyra, 1997)
In nine Vilnius Church Slavonic manuscripts, there are 14 words of Grigory Tsamblak in 18 copies on which an archeograpfical review was done.